2022
DOI: 10.1039/d1bm01719e
|View full text |Cite
|
Sign up to set email alerts
|

Physical confinement in alginate cryogels determines macrophage polarization to a M2 phenotype by regulating a STAT-related mRNA transcription pathway

Abstract: The immunologic response is considered to play a pivotal role in the application of biomaterial implants, and intrinsic properties of biomaterials can significantly modulate the anti-inflammatory effects. However, how physical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…The alginate cryogels showed a highly interconnected pore structure (Figure B). The average pore size was 204.9 ± 51.8 μm, and the porosity was 64.9 ± 5.6%, in accordance with our previous study . Compression tests were performed to investigate their mechanical properties.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The alginate cryogels showed a highly interconnected pore structure (Figure B). The average pore size was 204.9 ± 51.8 μm, and the porosity was 64.9 ± 5.6%, in accordance with our previous study . Compression tests were performed to investigate their mechanical properties.…”
Section: Resultssupporting
confidence: 80%
“…Thus, it is still a challenge to examine the influence of the direct cell-to-cell interplays between cancer cells and macrophages without disturbance from ECM components. Therefore, in this study, leveraging our experience in culturing cancer cells and TAMs in vitro using biomaterials, , we established a sequential culture method for the direct BCCs–TAMs coculture by using a 3D alginate cryogel matrix without introducing growth factors to retain M2-type TAM identity. This approach resulted in the recapitulation of direct crosstalk between two cell populations and enabled the elucidation of phenotype changes in proliferation (Figure ), stemness (Figure ), migration (Figure ), and ECM remodeling (Figure ) that occur within breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21] In addition, the ECM's loose structure with low physical confinement has been demonstrated to promote macrophage M2 polarization and foster a pro-regenerative environment by regulating a STAT-related mRNA transcription pathway. [22] Furthermore, ECM components, including collagen, laminin, and proteoglycan, can specifically recognize immune cell surface receptors, such as integrins, to mediate their adhesion and trafficking. [15,19,23] Numerous studies have indicated that cell adhesion behaviors play a critical role in regulating macrophage M2 polarization.…”
Section: Introductionmentioning
confidence: 99%